2011
DOI: 10.1128/jvi.05101-11
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Tropism of Influenza A Viruses: Identification of H7 Subtype-Specific Host Responses in Human Respiratory and Ocular Cells

Abstract: Highly pathogenic avian influenza (HPAI) H7 virus infection in humans frequently

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 47 publications
5
46
0
Order By: Relevance
“…H7 influenza viruses associated with human ocular disease have been previously shown to downregulate numerous genes related to NF-B signaling in lung epithelial cells compared with virus subtypes typically associated with respiratory disease (18,28). As A(H7N9) viruses have been associated with respiratory instead of ocular disease, we examined the induction of NF-B signaling related genes in Calu-3 cells following Anhui/1 virus infection and compared our findings to previously published data (Fig.…”
Section: A(h7n9) Virus Induces Differential Cytokine Production Inmentioning
confidence: 63%
See 4 more Smart Citations
“…H7 influenza viruses associated with human ocular disease have been previously shown to downregulate numerous genes related to NF-B signaling in lung epithelial cells compared with virus subtypes typically associated with respiratory disease (18,28). As A(H7N9) viruses have been associated with respiratory instead of ocular disease, we examined the induction of NF-B signaling related genes in Calu-3 cells following Anhui/1 virus infection and compared our findings to previously published data (Fig.…”
Section: A(h7n9) Virus Induces Differential Cytokine Production Inmentioning
confidence: 63%
“…It was previously shown that the transcriptomic response in human bronchial epithelial cells to A(H7N9) virus was more similar to the response to human H3N2 virus than to the response to either avian H5 or H7 subtype virus (45). We and others have shown previously that H7 subtype viruses associated with ocular disease in humans are generally highly infectious in human bronchial epithelial cells but elicit delayed and weakened induction of host inflammatory responses and NF-B signaling compared with H5N1 viruses (17,18,20,28). In contrast, while A(H7N9) viruses maintained the high infectivity and replicative ability in human bronchial epithelial cells observed with other H7 viruses ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations